Continuity and Change in Societies in Post-Socialist Transformation: Research into Households and the Economy - Schrader, Heiko (International Dialogues on Education Journal, 2019)
Starting from the distinction between short-term system transition (new institutional economics, political science) and system transformation as a long-term process of societal change, the author argues that institution-building is a long-term and complicated process and that informal institutions of everyday life do not change as quickly as the newly implemented formal ones. The author has a particular interest in the people’s economy of everyday life. He takes a look at three empirical research projects he conducted between 1997 and 2016, investigating whether informal institutions still undermine formal ones that are necessary for the functioning of a market economy. The research projects show particular characteristics. (1) a clear-cut double morality between bureaucracy and the rich, on the one hand, and the small people who have to protect themselves, on the other. (2) It is advantageous to know somebody in the lower bureaucracy (blat or other forms of bribery in everyday life). (3) Agents place strong reliance on personal face-to-face networks, including family networks, and avoid formal institutions. Indeed, many findings of the author support continuity even after almost 30 years of post-socialism, while some changes to the market society occur among better-off people.